Family Function Impacts Relapse Tendency in Substance Use Disorder: Mediated Through Self-Esteem and Resilience - Xia, Yuwei; Gong, Yu; Wang, Hanbin; Li, Shen; Mao, Fuqiang (Frontiers in Psychiatry, 2022)
Background: Substance abuse has been a public health concern, and even after detoxification treatment, the relapse rate is still high. Family function is closely related to substance dependence. However, the researches on psychological mechanisms between them are rare. Objectives: We aimed to explore the mediating role of self-esteem and resilience in the pathway that family function impacts the relapse tendency among patients with substance use disorder (SUD). Methods: A total of 282 SUD patients were recruited, and standard questionnaires were administered for each patient. The relapse tendency, family function, self-esteem and resilience were assessed by the family care index questionnaire, the Connor-Davidson resilience scale, the Rosenberg self-esteem scale and the relapse tendency questionnaire. Bootstrap method was conducted for mediation analysis to test the effects of how family function affects relapse tendency mediated through self-esteem and resilience. Results: The average score of relapse tendency of the patients was 28.47 (SD=11.89). Intermediary analysis found that self-esteem played an intermediary role in the relationship between family function and relapse tendency. Resilience plays an intermediary role in the relationship between family function and relapse tendency. Further, the path analysis showed that family function not only had a direct association with relapse tendency, but also indirectly related to relapse tendency through self-esteem and resilience. Conclusions：Self-esteem and resilience are the key factors in the relationship between family function and relapse tendency of SUD patients.